Lung washout during spontaneous breathing: Parameter estimation with a time-varying model - Saidel, Gerald M.; Saniie, Jafar; Chester, Edward H. (Computers and biomedical research, 1980)
We use a time-varying model to analyze the multibreath washout of nitrogen from lungs of human subjects breathing spontaneously. Based on standard pulmonary function evaluation, the 39 subjects tested are classified in the following categories: nonsmoking normal, “smoking” normal, asthma, diffuse interstitial lung disease, and chronic obstructive lung disease. The degree of ventilation inhomogeneity among these subjects was indicated by two independent parameters of the model, which were estimated by nonlinear optimization. A Gauss-Newton algorithm with a Marquardt modification was applied to a least-squares objective function. Constraints were included in a penalty function. Values of the model parameters from repeated washouts of the same subjects showed wide variability. Also, model parameters did not appear to provide any better distinction among clinical groups than did a moment ratio whose computation is much less expensive and more reliable.